A Study Of Novelty-Seeking-Based Revisiting Interest at Ketep Pass Tourism Object in Magelang Regency - Endang Swastuti; Emiliana Sri Pudjiarti (Universitas Kuningan, 2018)
The purpose of this study was to identify a model of relationship between novelty seeking based tourism, service quality and destination image toward tourists' satisfaction and tourists' revisiting in the Ketep Pass area of Magelang Regency. Data collection used a survey through questionnaires, observation and interviews of 249 domestic and foreign tourists with purposive sampling technique. Data were analyzed by structural equation model to test the hypothesis. The results of the study prove that novelty seeking based tourist attraction, service quality and destination image give significant influence on tourists' satisfaction and revisiting. This condition explains that the diversity of potential tourist attractions in the Magelang Regency Ketep Pass area can be developed as a new tourist destination (novel atraction) on the Solo-Selo-Borobudur (SSB) route with the characteristic of the mountain tourism namely Mount Merapi. This new tourist attraction is able to provide meaningful benefits for tourists in the form of enrichment values, self-development, challenge or adventure, as well as new knowledge or insight even though sometimes full of risks.